Energy technological progress, energy consumption, and CO2 emissions: Empirical evidence from China. (1st November 2019) - Gu, Wei; Zhao, Xiaohui; Yan, Xiangbin; Wang, Chen; Li, Qing
Abstract: Technical progress is usually considered to be an important way to effectively reduce carbon emissions. However, the advancement of energy technology may cause rebound effect which may lessen the emission reduction effect of technical progress. This suggests that the real impact of energy technological progress is worthy of further study. By taking the rebound effect into consideration, this study estimates the real effect of energy technological progress and energy consumption on carbon emissions in China, based on an interaction model, and using data from China's 30 provinces for the period 2005–2016. Key results include the following: (1) An inverted U-shaped relationship between energy technological progress and carbon emissions is detected. (2) Across technical progress, energy consumption has an inverted U-shaped effect on carbon emissions. (3) Turning points are found in both the direct effect and the technical effect of China's energy technological progress. This indicates that they initially increase carbon emissions, and then reduce them, although the rebound effect continues to have a positive impact on the increase of carbon emissions. (4) The largest differences between regions with different energy technology levels appear in the direct effect and the technical effect of energy technological progress on CO2 emissions, and there is almost no difference in rebound effect. Some relevant policy recommendations are proposed, based on the above findings. Highlights: Double-logarithmic dynamic panel model is applied to calculate carbon elasticity. Nonlinear effects of technical progress and energy consumption are found. Inverted U-shaped effects of energy technological progress is identified. Direct, rebound, and technical effects of technical progress are analyzed. The effects of energy technological progress on CO2 emissions vary across regions.